The politics of social ties immigrants in an ethnic homeland - Dragojevic, Mila (Ashgate Pub., 2014)
After forced migration to a country where immigrants form an ethnic majority, why do some individuals support exclusivist and nationalist political parties while others do not? Based on extensive interviews and an original survey of 1200 local Serbs and ethnic Serbian refugees fleeing violent conflict in Bosnia and Croatia.